Investigation of Dimensions of Social-Emotional Classroom Behavior and School Readiness for Low-Income Urban Preschool Children. - Fantuzzo, John W.; Bulotsky‐Shearer, Rebecca J.; McDermott, Paul A., 1945-; McWayne, Christine M.; Frye, Douglas.; Perlman, Staci. (Tufts University. Tisch Library., 2019)
The present study identified higher order relationships among teacher assessments of approaches to learning and emotional and behavioral adjustment constructs for low-income urban preschool children. It examined the unique contribution of these dimensions to cognitive and social competencies and risk of poor academic outcomes. Analyses of a large representative sample of urban Head Start children revealed two distinct and reliable higher order dimensions of classroom adjustment behavior: regulated and academically disengaged behavior. Both dimensions contributed unique variance to the prediction of early mathematics ability and general classroom competencies before kindergarten entry, controlling for child demographics. Each dimension also contributed independently to the prediction of academic risk, controlling for child demographics. Implications for practice and policy are discussed.